(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: It remains poorly understood what should be the temperature of the irrigating solution for intraocular surgery and how long it is reasonable to use irrigating solutions during vitrectomy. Purpose: To investigate the structure of the rabbit chorioretinal complex after vitrectomy with the use of irrigating solutions having different temperatures for 30 minutes. Materials and Methods: Twelve Chinchilla rabbits (24 eyes) were divided into two experimental groups and one control group. The two experimental groups, each of 5 rabbits (10 eyes), underwent a three-port pars plana vitrectomy with either 22°C or 5°C irrigating solution. Two intact rabbits (4 eyes) were used as controls for comparison. The duration of irrigation/aspiration was 30 minutes. The material for histology was obtained at days 1 and 7 after surgery, and the chorioretinal complex was histologically examined by light microscopy. Results: Groups of animals subjected to thirty-minute vitreous cavity cooling with the 22 °C or 5°С irrigating solution showed no structural changes in the retinal and choroidal components compared to intact animals. Conclusion: The 22 °C or 5°С irrigating solution produces no structural changes in the retina and choroid, and can be used in the vitreoretinal surgical procedure for continuous vitreous cavity irrigation lasting for up to 30 minutes.